Anomalous origin of the right pulmonary artery from the ascending aorta associated with aortopulmonary window. Issue 2 (April 1978) - Gula, G; Chew, C; Radley-Smith, R; Yacoub, M
Abstract : A rare case of anomalous origin of the right pulmonary artery from the ascending aorta associated with an aortopulmonary window and severe pulmonary hypertension in a 13-year-old girl is reported. The window was closed using a Dacron patch and the continuity between the anomalous vessel and the main pulmonary artery was restored with a tubular Dacron graft. After operation the pulmonary pressure dropped to about one-half of the systemic pressure, and equal perfusion and ventilation of both lungs was demonstrated. Although early recognition and surgical treatment of this condition are mandatory to prevent the onset of irreversible pulmonary vascular disease, the presence of severe pulmonary hypertension did not contraindicate surgical correction in our patient.